2019
DOI: 10.1136/ijgc-2018-000011
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in ovarian cancer: fake news or the real deal?

Abstract: Cancer immunotherapy has emerged as one of the most promising approaches in oncology, and comprises the activation of the immune system to induce tumor immune surveillance or to reverse the tumor immune escape. Different therapeutic strategies for ovarian carcinoma have evolved over the years. Already 30 years ago, the first clinical studies focused on modulating the tumor cytokine network with special attention to interferon-mediated immune responses. With the exploration of specific tumor antigens such as NY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 51 publications
0
34
0
1
Order By: Relevance
“…For detailed reviews of antibody-based immunotherapies for ovarian cancer see Tse et al, 2014 [ 200 ] and Drerup et al, 2015 [ 201 ]. For more recent reviews of immune therapies for ovarian cancer with engineered T-cells, TCRs, and CAR-T cells see Marth et al, 2019 [ 8 ]; Fan et al, 2018 [ 53 ]; Rodriguez et al, 2018 [ 73 ]; Zhu et al, 2017 [ 202 ]; Rodriguez-Garcia et al, 2017 [ 203 ]; Gaillard et al, 2016 [ 52 ]; Alipour et al, 2016 [ 204 ]. These include summaries of recruiting and ongoing clinical trials targeting immune checkpoint inhibitors or various antigens including, NY-ESO-1, HER2, FR-alpha, MSLN, MUC16 (CA125), EGFR, CD133, CEA, NKG2D, MAGE-A4, WT-1, and p53.…”
Section: Agents and Strategies For Cancer Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…For detailed reviews of antibody-based immunotherapies for ovarian cancer see Tse et al, 2014 [ 200 ] and Drerup et al, 2015 [ 201 ]. For more recent reviews of immune therapies for ovarian cancer with engineered T-cells, TCRs, and CAR-T cells see Marth et al, 2019 [ 8 ]; Fan et al, 2018 [ 53 ]; Rodriguez et al, 2018 [ 73 ]; Zhu et al, 2017 [ 202 ]; Rodriguez-Garcia et al, 2017 [ 203 ]; Gaillard et al, 2016 [ 52 ]; Alipour et al, 2016 [ 204 ]. These include summaries of recruiting and ongoing clinical trials targeting immune checkpoint inhibitors or various antigens including, NY-ESO-1, HER2, FR-alpha, MSLN, MUC16 (CA125), EGFR, CD133, CEA, NKG2D, MAGE-A4, WT-1, and p53.…”
Section: Agents and Strategies For Cancer Immunotherapymentioning
confidence: 99%
“…Serious side-effects, however, were also seen in some patients, particularly inflammation [ 290 ]. Such immune-related toxicities are thought to be due to indiscriminate activation of auto-reactive T-cells, which are usually supressed via these molecules [ 8 ]. Only 2 patients out of 40 with recurrent platinum sensitive ovarian cancer completed a phase 2 clinical trial with Ipilimumab monotherapy (NCT01611558), with failure to complete mostly due to study drug toxicity or disease progression [ 291 ].…”
Section: Agents and Strategies For Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Today, probably another promising therapeutic approach in this context is the blockade of immune checkpoints, such as programmed cell death 1 (PD-1), its ligand PD-L1 or cytotoxic T-lymphocyte associated protein 4 (CTLA4), which demonstrated impressive response rates in malignant melanoma and non-small-cell lung carcinoma (NSCLC). Considering this and a positive expression of check point molecules in OC which is associated with clinical outcome [41] many clinical studies investigate check point inhibitors in OC, especially platinum-resistant or recurrent OC [42]. Various simultaneous anti-angiogenics may improve the therapeutic benefit and counteract compensatory escape mechanisms [43].…”
Section: Concepts To Overcome Drug Resistancementioning
confidence: 99%
“…Recently, studies showed that immune responses have close relationships with ovarian cancer progression [6] . At present, some pre-clinical trials targeting immune cells in the ovarian cancer microenvironment have been performed.…”
Section: Introductionmentioning
confidence: 99%